From categories to categorization : studies in sociology, organizations and strategy at the crossroads - Durrand, Rodolphe; Granqvist, Nina; Tyllström, Anna (Emerald Publishing Limited, 2017)
Categorization pervades economic life; products, services, firms and industries are continuously being classified by rivals, clients, experts and critics. A stream of research highlighting the importance of market and product categories for organizations and individuals has grown in importance during the past 40 years. This volume contains ten essays on categorization authored by some of the world's leading scholars within sociology of markets, organization theory, and strategy research. It opens with revisiting the influential theory of the categorical imperative, and moves on to present various accounts of the social processes that form part of categorization and elaboration of their consequences. Together, the different chapters effectively show that categorization is a process, tightly connected to actors involved and their specific acts, the characteristics of the entity being categorized, and the context and timing informing these activities. As such, it complements the earlier cognitive perspectives by discussing the evaluative, social, and political manifestations of categorization.
Includes index.
Keywords: Organizational sociology.; Organizational behavior.; Business & Economics -- Organizational Behavior.; Organizational theory & behaviour.; elektronické knihy; electronic books